2010
DOI: 10.1021/es1019614
|View full text |Cite
|
Sign up to set email alerts
|

Partition of Environmental Chemicals between Maternal and Fetal Blood and Tissues

Abstract: Passage of environmental chemicals across the placenta has important toxicological consequences, as well as for choosing samples for analysis and for interpreting the results. To obtain systematic data, we collected in 2000 maternal and cord blood, cord tissue, placenta, and milk in connection with births in the Faroe Islands, where exposures to marine contaminants is increased. In 15 sample sets, we measured a total of 87 environmental chemicals, almost all of which were detected both in maternal and fetal ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
225
6
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 348 publications
(278 citation statements)
references
References 40 publications
33
225
6
2
Order By: Relevance
“…The maternal serum concentration of PFASs before GA 16 weeks was used as proxy for prenatal exposure since PFAS has been shown to cross the placenta (Gützkow et al 2012;Needham et al 2011). Serum concentrations of PFAS are known to decrease throughout pregnancy, but PFAS measurements at different time points during pregnancy are highly correlated (Glynn et al 2012) and the compounds have long half-lives of 4-5 years (Olsen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maternal serum concentration of PFASs before GA 16 weeks was used as proxy for prenatal exposure since PFAS has been shown to cross the placenta (Gützkow et al 2012;Needham et al 2011). Serum concentrations of PFAS are known to decrease throughout pregnancy, but PFAS measurements at different time points during pregnancy are highly correlated (Glynn et al 2012) and the compounds have long half-lives of 4-5 years (Olsen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The most common types are PFOS (perfluorooctane sulfonic acid), and PFOA (perfluorooctanoic acid), which are ubiquitously present in human serum, where they show an estimated elimination half-life of four years for PFOA and five years for PFOS (Calafat et al 2007;Kato et al 2011;Olsen et al 2007). They cross the placenta (Needham et al 2011) and are released through human milk (Mogensen et al 2015), thereby causing early-life exposure that may be worthy of concern. Due to changes in production, serum concentrations of some PFASs have decreased, although others have increased, including perfluorohexane sulfonic acid (PFHxS,) perfluorononanoic acid (PFNA), and perfluorodecanoic acid (PFDA) (Glynn et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the research reports also demonstrated that the fluoride also transferred to the infant through human breast milk 32 . That means during foetal life and early infancy, the blood brain barrier provides only partial protection against the entry of chemicals into the central nervous system 33,34 .…”
Section: Discussionmentioning
confidence: 91%
“…Fetus is not well protected against fluoride that circulates in the maternal blood. This is due to placenta does not block the passage of fluoride from maternal circulation to foetal circulation 32 and poorly developed blood brain barrier (BBB). The poorly formed BBB vasculature fails to control the entry of fluoride into the brain 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of both ΣPCB and p,p’ -DDE were found to be higher in Cohort 3 compared to Cohorts 1 and 5 (Table 1). However, maternal lipid based serum concentrations have been shown to be 1.7 times those found in the corresponding cord serum samples [36] and the lower concentrations in Cohort 1 can, thus, be attributed to the measures being performed on cord blood rather than maternal serum. Methylmercury concentrations were found to be the highest in Cohort 1 and lowest in Cohort 5.…”
Section: Resultsmentioning
confidence: 99%